Water-based environment-friendly epoxy paint and preparation method thereof
Patent Information
- Application Number
- CN202610838715.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-06-11
Abstract
Description
Technical Field
[0001] This invention relates to the field of water-based coatings technology, specifically to a water-based environmentally friendly epoxy paint and its preparation method. Background Technology
[0002] With increasingly stringent environmental regulations, traditional solvent-based coatings are gradually being restricted due to their high VOC content, making water-based coatings a hot topic in research and application. Electrical equipment such as substations, control cabinets, and distribution boxes operate in complex environments for extended periods, requiring coatings to possess multiple functions simultaneously, including moisture and water resistance, rust prevention, high adhesion, insulation, flame retardancy, and high-temperature resistance.
[0003] Existing water-based coatings, such as CN112266679B, disclose a flame-retardant and waterproof water-based core-shell acrylic resin coating. However, it is mainly used in the construction, wood, and leather industries, and has limited rust prevention and adhesion to metal substrates. Furthermore, its flame retardant system is intumescent and does not address insulation properties. While other water-based epoxy paints have certain advantages in adhesion, they still fall short in terms of multi-performance synergy, such as waterproofing, insulation, and flame retardancy. Summary of the Invention
[0004] The purpose of this invention is to provide a water-based environmentally friendly epoxy paint that addresses the shortcomings and deficiencies of existing technologies.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: a water-based environmentally friendly epoxy paint, composed of component A and component B in a weight ratio of 100:15-30; wherein, component A comprises the following raw materials in parts by weight: 40-65 parts of water-based epoxy resin emulsion; 10-20 parts of modified core-shell structure acrylate copolymer; 3-8 parts of polyaniline-modified zinc phosphate; 5-12 parts of composite flame retardant; 0.5-2.0 parts of wetting and dispersing agent; 0.2-1.0 parts of defoamer; and 10-25 parts of deionized water; component B comprises the following raw materials in parts by weight: 80-95 parts of water-based epoxy curing agent; and 5-15 parts of adhesion promoter.
[0006] A further improvement is that the modified core-shell structured acrylate copolymer is a core-shell structured emulsion with methyl methacrylate as the core and butyl acrylate-hydroxyethyl acrylate-vinyltriethoxysilane copolymer as the shell, and its glass transition temperature is -10℃ to 15℃, and its solid content is 40% to 50%.
[0007] A further improvement is that the preparation method of the polyaniline-modified zinc phosphate is as follows: zinc phosphate is dispersed in an aqueous ethanol solution, aniline monomer and ammonium persulfate are added, and the polymerization reaction is carried out at 0-5°C for 4-8 hours. After filtration, washing and drying, polyaniline-coated zinc phosphate composite particles are obtained.
[0008] A further improvement is that the composite flame retardant is composed of the following components in parts by weight: 30-50 parts of aluminum diethylphosphinic acid, 20-40 parts of melamine polyphosphate, 10-20 parts of zinc borate, and 5-15 parts of expanded graphite.
[0009] A further improvement is that the adhesion promoter is... A mixture of glycidyl etheroxypropyltrimethoxysilane and titanate coupling agent in a weight ratio of 3:1 to 1:1.
[0010] A further improvement is that the wetting and dispersing agent is a polyether-modified polysiloxane, and the defoamer is a polyether-modified organosilicon defoamer.
[0011] A method for preparing a water-based environmentally friendly epoxy paint includes the following steps: (1) Preparation of component A: Mix deionized water, wetting and dispersing agent and defoamer evenly according to the formula. Add polyaniline modified zinc phosphate and composite flame retardant in sequence under stirring. Disperse at high speed for 30-60 min until fineness ≤30μm. Then adjust the stirring speed, add waterborne epoxy resin emulsion and modified core-shell structure acrylate copolymer, continue stirring for 20-40 min, and filter out the material. (2) Preparation of component B: Mix the water-based epoxy curing agent and adhesion promoter evenly and stir for 10-20 minutes; (3) When using, mix component A and component B evenly in proportion and let stand for 10 to 20 minutes to mature.
[0012] A further improvement is that the high-speed dispersion speed in step (1) is 1500-2500 rpm, and the filtration uses a 200-mesh filter.
[0013] After adopting the above technical solution, the beneficial effects of the present invention are as follows: 1. A dense cross-linked network is formed by blending waterborne epoxy resin emulsion with modified core-shell structured acrylate copolymer. The vinyltriethoxysilyl groups introduced into the core-shell copolymer can undergo hydrolytic condensation, further improving the sealing and hydrophobicity of the coating. Testing shows that the coating exhibits water resistance for over 240 hours without blistering or peeling, effectively preventing moisture penetration and meeting the requirements for long-term use in humid or condensing environments.
[0014] 2. Polyaniline-modified zinc phosphate is used to replace traditional chromium-containing anti-rust pigments. Polyaniline can induce the formation of a dense passivation film on the metal surface, while zinc phosphate provides long-term corrosion inhibition. The two work synergistically to achieve a combination of active and passive rust prevention. Tests show that the coating withstands over 500 hours of salt spray, with no red rust spreading at the cross-sections, significantly outperforming ordinary water-based acrylic coatings in protecting metal substrates.
[0015] 3. Waterborne epoxy resin exhibits excellent wettability on metal substrates. Combined with the adhesion promoter in component B, it can form chemical bonds at the coating-metal interface, significantly improving both dry and wet adhesion. Testing shows that the cross-cut adhesion is ≤0 grade, maintaining strong adhesion even in high humidity environments, thus overcoming the deficiency of insufficient adhesion of existing waterborne coatings to metal surfaces.
[0016] 4. After curing, the epoxy resin forms a three-dimensional network structure with inherently high volume resistivity. Zinc borate in the composite flame retardant further enhances the electrical insulation of the coating. Testing shows that the coating's volume resistivity is ≥ It meets the insulation protection requirements of the substation cabinet and can effectively prevent leakage and short circuit risks.
[0017] 5. The composite flame retardant adopts a phosphorus-nitrogen-boron-graphite synergistic system of aluminum diethylphosphonate, melamine polyphosphate, zinc borate, and expanded graphite: during combustion, the phosphorus and nitrogen components promote char formation, zinc borate enhances the density of the char layer, and expanded graphite expands upon heating to form a physical insulation layer, synergistically achieving highly efficient flame retardancy. Testing shows that the flame retardancy rating reaches UL94V-0, and after baking at 300℃ for 1 hour, the coating remains intact without cracking or peeling, demonstrating excellent fire resistance and high-temperature resistance. Detailed Implementation
[0018] The technical solution adopted in this specific embodiment is: a water-based environmentally friendly epoxy paint, which is composed of component A and component B in a weight ratio of 100:15-30; Component A comprises the following raw materials in parts by weight: 40-65 parts of waterborne epoxy resin emulsion; 10-20 parts of modified core-shell structured acrylate copolymer; 3-8 parts of polyaniline-modified zinc phosphate; 5-12 parts of composite flame retardant; 0.5-2.0 parts of wetting and dispersing agent; Defoamer 0.2-1.0 parts; deionized water 10-25 parts; All performance indicators in this invention were tested in accordance with the following national or industry standards: Adhesion (dry / wet): Tested according to GB / T9286-1998 "Paints and Varnishes Cross-cut Test", with a 1mm spacing and a rating of 0 to 5.
[0019] Water resistance: According to GB / T1733-1993 "Test Method for Water Resistance of Coating Film", the coating test panel was immersed in distilled water at (23±2)℃ and the bubbling, loss of gloss and peeling were observed.
[0020] Salt spray resistance: According to GB / T1771-2007 "Determination of resistance to neutral salt spray of paints and varnishes", cross-marking is performed, and the time of red rust appearance is recorded. Insulation resistance (volume resistivity): According to GB / T1410-2006 "Test methods for volume resistivity and surface resistivity of solid insulating materials", a three-electrode system is used, and a DC voltage of 500V is applied.
[0021] Flame retardancy rating: V-0, V-1, and V-2 ratings are determined according to the vertical burning method of UL94 "Test for flammability of plastic materials in equipment and appliance parts".
[0022] Limiting Oxygen Index (LOI): Determined according to GB / T2406.2-2009 "Oxygen Index Method for Plastics - Determination of Combustion Behavior".
[0023] Low temperature bending test: The test shall be conducted at -20℃ in accordance with GB / T6742-2007 "Bending test of paint and varnish (cylindrical shaft)".
[0024] Contact angle: According to GB / T30693-2014 "Measurement of contact angle between plastic film and water", the static drop method was used.
[0025] Interfacial shear strength: in accordance with GB / T7124-2008 "Determination of tensile shear strength of adhesives".
[0026] Peak heat release rate: in accordance with GB / T16172-2007 "Test Method for Heat Release Rate of Building Materials".
[0027] Waterborne epoxy resin emulsion provides the skeletal structure of the coating, giving it excellent adhesion, insulation and chemical corrosion resistance; modified core-shell structure acrylate copolymers serve as toughening modifiers, introducing silane crosslinking points to improve the coating's flexibility and sealing and waterproofing; polyaniline-modified zinc phosphate provides both active rust prevention and passive corrosion inhibition; composite flame retardants achieve synergistic flame retardancy of phosphorus-nitrogen-boron-graphite.
[0028] If there is too little epoxy, the adhesion will be insufficient; if there is too much, the coating will be brittle. If there is too little core-shell copolymer, the flexibility will be poor; if there is too much, the insulation will be reduced. Rust inhibitors and flame retardants can be evenly dispersed within a certain range without agglomeration, achieving the best balance of five properties: waterproof, rustproof, adhesion, insulation, and flame retardant.
[0029] After experimental verification, when the waterborne epoxy resin emulsion is 40 parts, the modified core-shell structured acrylate copolymer is 10 parts, the polyaniline-modified zinc phosphate is 3 parts, and the composite flame retardant is 5 parts, the adhesion is grade 0, the water resistance is 216h without abnormalities, the salt spray resistance is 500h, and the insulation resistance is [missing information]. The flame retardant rating is UL94V-0. When the composition is 55 parts waterborne epoxy resin emulsion, 15 parts modified core-shell structured acrylate copolymer, 5 parts polyaniline-modified zinc phosphate, and 8 parts composite flame retardant, the adhesion is grade 0, the water resistance is normal for 240 hours, the salt spray resistance is 550 hours, and the insulation resistance is [missing information]. The flame retardant rating is UL94V-0. When the composition is 65 parts waterborne epoxy resin emulsion, 20 parts modified core-shell structured acrylate copolymer, 8 parts polyaniline-modified zinc phosphate, and 12 parts composite flame retardant, the adhesion is grade 0, the water resistance is normal for 228 hours, the salt spray resistance is 520 hours, and the insulation resistance is [missing information]. The flame retardant rating is UL94V-0. When the composition is 35 parts waterborne epoxy resin emulsion, 15 parts modified core-shell structured acrylate copolymer, 5 parts polyaniline-modified zinc phosphate, and 8 parts composite flame retardant, the adhesion is grade 1, the water resistance is 168h, the salt spray resistance is 400h, and the insulation resistance is [missing information]. It has a flame retardant rating of UL94V-1.
[0030] In summary, component A of this invention exhibits excellent overall performance within the defined proportions. The optimal formulation comprises 55 parts epoxy resin, 15 parts core-shell copolymer, 5 parts rust inhibitor, and 8 parts flame retardant. Exceeding these proportions significantly reduces adhesion, water resistance, salt spray resistance, insulation resistance, and flame retardancy.
[0031] Component B comprises the following raw materials in parts by weight: 80-95 parts of water-based epoxy curing agent; 5-15 parts of adhesion promoter.
[0032] Waterborne epoxy curing agents undergo ring-opening crosslinking reactions with epoxy resins to form a three-dimensional network structure, which is the foundation for coating adhesion, water resistance, and insulation. Adhesion promoters form chemical bridges at the interface, significantly improving wet adhesion. Insufficient curing agent results in incomplete crosslinking, leading to a soft coating with poor water resistance; excessive curing agent causes residual amine groups to absorb water, reducing insulation and water resistance. Insufficient adhesion promoters result in insufficient wet adhesion; excessive promoters reduce coating density. Within a suitable mixing ratio, both exhibit a synergistic effect, achieving the optimal balance between adhesion, water resistance, and insulation performance.
[0033] After experimental verification, when the water-based epoxy curing agent is 80 parts and the adhesion promoter is 5 parts, the dry adhesion is grade 0, the wet adhesion is grade 1, the water resistance is normal after 216 hours, and the insulation resistance is [missing information]. ; When the water-based epoxy curing agent is 90 parts and the adhesion promoter is 10 parts, the dry adhesion is grade 0, the wet adhesion is grade 0, the water resistance is normal after 240 hours, and the insulation resistance is... ; When the water-based epoxy curing agent is 95 parts and the adhesion promoter is 15 parts, the dry adhesion is grade 0, the wet adhesion is grade 0, the water resistance is normal after 228 hours, and the insulation resistance is... ; When the water-based epoxy curing agent is 70 parts and the adhesion promoter is 10 parts, the dry adhesion is grade 1, the wet adhesion is grade 2, the water resistance is 168h, and the insulation resistance is [missing information]. .
[0034] In summary, component B of this invention exhibits excellent overall performance within the defined proportions. The optimal ratio is 90 parts curing agent and 10 parts adhesion promoter. Exceeding this range results in a significant decrease in adhesion, water resistance, and insulation resistance.
[0035] Component A provides epoxy resin and functional fillers, while component B provides curing agents and coupling agents. Within the A:B ratio of 100:15 to 30, the stoichiometric ratio of epoxy groups to amine groups is close to the theoretical equivalence ratio, ensuring a complete and thorough crosslinking reaction. If the ratio is too low, for example, too little component B, curing will be insufficient, resulting in a soft coating with poor water resistance and low insulation. If the ratio is too high, for example, too much component B, residual amine groups will absorb water and swell, leading to decreased adhesion and reduced insulation resistance.
[0036] After experimental verification, when A:B=100:15, the degree of crosslinking is 82%, the adhesion is grade 0, the water resistance is normal after 240 hours, and the insulation resistance is [value missing]. The pencil's hardness is H; When A:B = 100:20, the degree of crosslinking is 85%, the adhesion is grade 0, the water resistance shows no abnormalities after 240 hours, and the insulation resistance is... The pencil has a hardness of H. When A:B = 100:30, the degree of crosslinking is 87%, the adhesion is grade 0, the water resistance shows no abnormalities after 240 hours, and the insulation resistance is... The pencil's hardness is H; When A:B = 100:10, the degree of crosslinking is 72%, the adhesion is grade 1, blistering occurs after 240 hours of water resistance, and the insulation resistance is... The pencil has a hardness of HB.
[0037] In summary, coatings with an A:B ratio of 100:15 to 30 exhibit excellent overall performance, with 100:20 being the optimal ratio. Beyond this range, cross-linking becomes incomplete, resulting in a significant decrease in adhesion, water resistance, and insulation resistance.
[0038] The modified core-shell structured acrylate copolymer is a core-shell structured emulsion with methyl methacrylate as the core and butyl acrylate-hydroxyethyl acrylate-vinyltriethoxysilane copolymer as the shell. Its glass transition temperature is -10℃ to 15℃ and its solid content is 40% to 50%.
[0039] The modified core-shell copolymer, with methyl methacrylate as the core and acrylate copolymer containing vinyltriethoxysilane as the shell, has a glass transition temperature controlled between -10℃ and 15℃. This not only endows the coating with appropriate flexibility and resistance to low-temperature cracking, but also enhances the interfacial bonding between the coating and the metal substrate and the overall sealing and waterproofing through the hydrolysis and condensation reaction of silane groups.
[0040] Methyl methacrylate (PMMA) serves as the hard core to provide structural support, while butyl acrylate-hydroxyethyl acrylate-vinyltriethoxysilane copolymer forms the soft shell to impart flexibility. During film formation, the silane groups hydrolyze to silanols (-Si-OH), which condense with hydroxyl groups on the metal surface to form Si-OM covalent bonds. Simultaneously, silanols condense with each other to form a Si-O-Si network, significantly enhancing interfacial adhesion and the coating's sealing and waterproofing properties. The glass transition temperature (Tg) is controlled between -10℃ and 15℃ to maintain the coating's flexibility at low temperatures and prevent cracking.
[0041] After experimental verification, when using ordinary acrylate copolymer (silane-free, Tg=5℃), the wet adhesion is grade 1, the water resistance is 192h, micro-cracks appear in the low temperature bending test at -20℃, and the contact angle is 78°. When the modified core-shell structure copolymer of the present invention (containing silane, Tg=15℃) is used, the wet adhesion is grade 0, the water resistance is 240h without abnormality, the low temperature bending test (-20℃) shows no cracks, and the contact angle is 93°. When the modified core-shell structure copolymer of the present invention (containing silane, Tg=5℃) is used, the wet adhesion is grade 0, the water resistance is no abnormality for 240h, the low temperature bending test at -20℃ shows no cracks, and the contact angle is 95°. When the modified core-shell structure copolymer of the present invention (containing silane, Tg=-10℃) is used, the wet adhesion is grade 0, the water resistance is no abnormality for 240h, the low temperature bending test at -20℃ shows no cracks, and the contact angle is 94°. Without the addition of any core-shell copolymer, the wet adhesion is grade 2, the water resistance is blistering after 120 hours, the low-temperature bending test shows cracking at -20℃, and the contact angle is 68°.
[0042] In summary, the modified core-shell structured acrylate copolymer of this invention, containing silane groups, exhibits significantly better wet adhesion, water resistance, low-temperature crack resistance, and hydrophobicity than solutions without core-shell copolymers or those containing ordinary acrylate copolymers when the Tg is controlled within the range of -10℃ to 15℃. A Tg of 5℃ is the optimal solution. Beyond this Tg range (Tg=20℃), the low-temperature crack resistance and water resistance decrease significantly.
[0043] The preparation method of polyaniline-modified zinc phosphate is as follows: zinc phosphate is dispersed in an ethanol aqueous solution, aniline monomer and ammonium persulfate are added, and polymerization reaction is carried out at 0-5℃ for 4-8 hours. After filtration, washing and drying, polyaniline-coated zinc phosphate composite particles are obtained. Compared with simple physical mixing, the core-shell structure of polyaniline-modified zinc phosphate prepared by in-situ polymerization can significantly improve the dispersion stability and active passivation efficiency of the rust-inhibiting component, thereby improving salt spray resistance by more than 30%.
[0044] Polyaniline was coated onto the surface of zinc phosphate using in-situ polymerization to form core-shell structured composite particles. This structure offers three main advantages: firstly, the conductivity of polyaniline can induce redox reactions on the metal surface, forming... or A dense passivation film provides active rust prevention; secondly, zinc phosphate is released slowly. ,and The process involves three main aspects: first, the formation of insoluble complexes for passive rust prevention; second, the core-shell structure to prevent polyaniline agglomeration and improve dispersion stability; and third, low-temperature polymerization at 0–5℃ to control the appropriate molecular weight of polyaniline and ensure uniform coating.
[0045] After experimental verification, when the polyaniline-modified zinc phosphate (in-situ polymerization, 3 parts added) of the present invention is used, the salt spray resistance time is 510h, the rust width at the cross-shaped part is 1.0mm, and the dispersion stability is uniform and stable. When the polyaniline-modified zinc phosphate (in-situ polymerization, 5 parts added) of the present invention is used, the salt spray resistance time is 560h, the rust width at the cross-shaped part is 0.8mm, and the dispersion stability is uniform and stable. When the polyaniline-modified zinc phosphate (in-situ polymerization, 8 parts added) of the present invention is used, the salt spray resistance time is 540h, the rust width at the cross-shaped part is 0.9mm, and the dispersion stability is uniform and stable. When zinc phosphate and polyaniline are physically mixed (5 parts added), the salt spray resistance time is 430h, the rust width at the cross-shaped point is 1.4mm, and the dispersion stability shows some sedimentation.
[0046] In summary, the polyaniline-modified zinc phosphate prepared by in-situ polymerization of the present invention exhibits significantly improved dispersion stability compared to simple physical mixing, with the salt spray resistance time increasing from 430h to 510-560h, representing an improvement of 18.6%-30.2%, and the optimal addition amount is 5 parts.
[0047] The composite flame retardant consists of the following components in parts by weight: 30-50 parts aluminum diethylphosphinate, 20-40 parts melamine polyphosphate, 10-20 parts zinc borate, and 5-15 parts expanded graphite. This composite flame retardant, composed of aluminum diethylphosphinate, melamine polyphosphate, zinc borate, and expanded graphite, achieves UL94V-0 flame retardancy at relatively low dosages through the synergistic expansion and charring mechanism of phosphorus, nitrogen, boron, and graphite, as well as a physical heat insulation mechanism, while simultaneously enhancing the thermal stability and insulation of the coating.
[0048] Aluminum diethylphosphonate (phosphorus-based) decomposes during combustion to generate phosphoric acid / polyphosphoric acid, promoting char formation; melamine polyphosphate (nitrogen-based) decomposes to release non-combustible gases (ammonia, nitrogen), diluting oxygen and promoting the formation of a foamed char layer; zinc borate (boron-based) promotes char formation, suppresses smoke and dust, enhances the density of the char layer, and also has insulating properties; expanded graphite (graphite-based) expands 100–300 times in volume at high temperatures, forming a physical heat insulation layer that prevents heat transfer inward. All four components achieve highly efficient flame retardancy with low addition amounts.
[0049] After experimental verification, when the amount of the composite flame retardant of the present invention is 5 parts, the limiting oxygen index (LOI) is 29.8%, the UL94 rating is V-0, the char formation rate (600℃) is 30.1%, and the peak heat release is 142kW / m². When the amount of the composite flame retardant of the present invention is 8 parts, the LOI is 32.4%, the UL94 rating is V-0, the char formation rate is 34.6%, and the peak heat release is 108kW / m². When the amount of the composite flame retardant of the present invention added is 12 parts, the LOI is 33.5%, the UL94 rating is V-0, the char rate is 36.2%, and the peak heat release is 95kW / m². When 8 parts of aluminum diethylphosphinate and melamine polyphosphate are added, the LOI is 28.5%, the UL94 rating is V-0, the char formation rate is 24.3%, and the peak heat release is 195 kW / m².
[0050] In summary, the phosphorus-nitrogen-boron-graphite compound flame retardant of the present invention can achieve UL94V-0 flame retardancy at a low addition amount (5-12 parts). Compared with the phosphorus-nitrogen compound scheme, the char formation rate is increased by 23.9%-49.0%, and the peak heat release is reduced by 27.2%-44.6%. Among them, the addition amount of 8 parts is the optimal scheme.
[0051] Adhesion promoter is A mixture of glycidyl etheroxypropyltrimethoxysilane and titanate coupling agent in a weight ratio of 3:1 to 1:1. An adhesion promoter formulated with glycidyl etheroxypropyltrimethoxysilane and titanate coupling agent in a specific ratio can simultaneously form chemical bonds with epoxy resin, metal substrate and filler surface, producing a synergistic enhancement effect superior to a single coupling agent, and can maintain grade 0 adhesion even in high humidity environments.
[0052] The epoxy group undergoes a ring-opening reaction with the epoxy resin, and the methoxy group hydrolyzes to form silanol, which then condenses with the hydroxyl groups on the metal surface to form Si-O-Fe covalent bonds. Titanate coupling agents (such as NDZ-101) can simultaneously bond to both the filler surface and the resin matrix.
[0053] After experimental verification, when KH-560: titanate = 3:1, the dry adhesion is grade 0, the wet adhesion is grade 0, the adhesion after 500h of damp heat aging is grade 0, and the interfacial shear strength is 22.5MPa. When KH-560: titanate = 2:1, the dry adhesion is grade 0, the wet adhesion is grade 0, the adhesion after damp heat aging is grade 0, and the interfacial shear strength is 21.8 MPa. When KH-560: titanate = 1:1, the dry adhesion is grade 0, the wet adhesion is grade 0, the adhesion after damp heat aging is grade 1, and the interfacial shear strength is 20.6 MPa. When KH-560 is used alone, the dry adhesion is grade 0, the wet adhesion is grade 1, the adhesion after damp heat aging is grade 2, and the interfacial shear strength is 15.6 MPa.
[0054] In summary, when KH-560 and titanate are compounded in a ratio of 3:1 to 1:1, the wet adhesion and adhesion after damp heat aging remain at grade 0 to 1, and the interfacial shear strength reaches 20.6 to 22.5 MPa, which is significantly better than the single-use solution. Among them, KH-560:titanate = 3:1 is the most preferred solution.
[0055] The wetting and dispersing agent is a polyether-modified polysiloxane, and the defoamer is a polyether-modified silicone defoamer. The polyether-modified polysiloxane wetting and dispersing agent and defoamer effectively reduce the surface tension of the system, prevent filler agglomeration, and eliminate construction air bubbles, ensuring a coating fineness ≤30μm and a smooth, dense surface. Why can they effectively reduce the surface tension of the system, prevent filler agglomeration, and eliminate construction air bubbles, ensuring a coating fineness ≤30μm and a smooth, dense surface?
[0056] Polyether segments are hydrophilic, while polysiloxane segments are hydrophobic and have extremely low surface tension (approximately 21 mN / m), allowing them to rapidly migrate to the solid-liquid interface, reducing the system's surface tension and ensuring thorough wetting of the filler surface. Their anchoring groups adsorb onto the filler surface, and the polysiloxane segments extend into the liquid phase, creating steric hindrance and preventing filler re-agglomeration. The defoamer is also primarily composed of polyether-modified polysiloxanes, utilizing their incompatibility with the coating system to spread on the bubble surface, reduce the local surface tension of the bubble film, and cause the bubble to rupture.
[0057] After experimental verification, when the wetting and dispersing agent of the present invention is compounded with the defoamer, wherein the wetting and dispersing agent is 0.5 parts, the surface tension is 25.1 mN / m, the fineness (D90) is 30 μm, the bubble level is slight (level 1), and the coating appearance is smooth. When the wetting and dispersing agent of the present invention is compounded with the defoamer, wherein 1.0 part of the wetting and dispersing agent has a surface tension of 23.8 mN / m, a fineness (D90) of 28 μm, a bubble grade of 0, and a smooth, dense, and defect-free coating appearance; When the wetting and dispersing agent of the present invention is compounded with the defoamer, wherein the wetting and dispersing agent is 2.0 parts, the surface tension is 24.2 mN / m, the fineness (D90) is 27 μm, the bubble grade is 0, and the coating film has a smooth, dense and defect-free appearance. When no wetting and dispersing agent is added, but only an antifoaming agent is added, the surface tension is 51.8 mN / m, the fineness (D90) is 82 μm, the bubble level is slight grade 1, and the coating appearance shows pinholes and particles.
[0058] In summary, the polyether-modified polysiloxane wetting and dispersing agent of the present invention, when used in combination with an antifoaming agent, can reduce the surface tension to below 25 mN / m, achieve a fineness D90 ≤ 30 μm, and produce a smooth, dense, and defect-free coating. The optimal ratio is 1.0 part of the wetting and dispersing agent.
[0059] A method for preparing a water-based environmentally friendly epoxy paint includes the following steps: (1) Preparation of component A: Mix deionized water, wetting and dispersing agent and defoamer evenly according to the formula. Add polyaniline modified zinc phosphate and composite flame retardant in sequence under stirring. Disperse at high speed for 30-60 min until fineness ≤30μm. Then adjust the stirring speed, add waterborne epoxy resin emulsion and modified core-shell structure acrylate copolymer, continue stirring for 20-40 min, and filter out the material. (2) Preparation of component B: Mix the water-based epoxy curing agent and adhesion promoter evenly and stir for 10-20 minutes; (3) When using, mix component A and component B evenly in proportion and let stand for 10 to 20 minutes to mature.
[0060] By first mixing deionized water, wetting and dispersing agents, and defoamers, and then sequentially adding polyaniline-modified zinc phosphate and composite flame retardants for high-speed dispersion to a fineness ≤30μm, it is ensured that the solid fillers are fully wetted, depolymerized, and uniformly distributed in the system, avoiding agglomeration and thus guaranteeing a dense, smooth coating free of particle defects. Subsequently, waterborne epoxy resin emulsion and modified core-shell acrylate copolymer are added at a reduced rate to avoid damage to the polymer emulsion by high shear forces, maintaining the integrity of the latex particles and film-forming properties. Uniform compounding can be achieved simply by mixing the waterborne epoxy curing agent and adhesion promoter in component B, making the process simple and efficient.
[0061] When using, mix components A and B in the specified ratio and allow them to stand for 10–20 minutes to mature. This maturation process allows the epoxy resin and curing agent molecules to come into full contact and undergo a pre-crosslinking reaction, improving mixing uniformity and application adaptability. This ensures complete curing of the coating film and uniform crosslinking density, thereby guaranteeing the stable performance of the final coating's adhesion, water resistance, insulation, and flame retardant properties. The entire preparation process requires no complex equipment, operates under mild conditions (room temperature and pressure), and is easy for industrial production.
[0062] The preparation process of this invention adopts the design principle of "powder first, slurry later, high and low speed stepwise": first, deionized water, wetting and dispersing agent, and defoamer are mixed to pre-disperse the additives evenly in water; powder is added in sequence and dispersed at high speed to break up filler agglomerates using high-speed shear force; after the fineness meets the standard, polymer emulsion is added at a reduced speed to avoid high shear damaging latex particles; components A and B are mixed and matured for 10-20 minutes before use to allow epoxy groups and amine groups to fully contact and begin pre-crosslinking, ensuring uniform final crosslinking density.
[0063] After experimental verification, when using the preparation process of this invention and maturing for 10 minutes, the fineness is 28 μm, there is no demulsification, the adhesion is grade 0, the water resistance is normal after 240 hours, and the insulation resistance is [missing information]. ; When using the preparation process of this invention, after 15 minutes of curing, the fineness is 28 μm, there is no demulsification, the adhesion is grade 0, the water resistance is normal after 240 hours, and the insulation resistance is [value missing]. ; When using the preparation process of this invention, after 20 minutes of curing, the fineness is 28 μm, there is no demulsification, the adhesion is grade 0, the water resistance is normal after 240 hours, and the insulation resistance is [value missing]. ; When A and B are mixed and applied directly without curing, the fineness is 30μm, there is no demulsification, the adhesion is grade 1, slight loss of gloss occurs after 240 hours of water resistance, and the insulation resistance is... .
[0064] In summary, the preparation process of this invention, including a 10-20 minute ripening step, can achieve a fineness ≤30μm, no demulsification, adhesion grade 0, no abnormalities in water resistance for 240 hours, and insulation resistance ≥ This method is significantly superior to the method without a curing process. A curing time of 15 minutes is the optimal choice.
[0065] In step (1), the high-speed dispersion speed is 1500-2500 rpm, and a 200-mesh filter is used for filtration.
[0066] Controlling the high-speed dispersion rotation speed within the range of 1500–2500 rpm provides sufficient shear force to break up filler agglomerates and achieve submicron-level dispersion (fineness ≤30μm), while avoiding excessive heat generation or polymer emulsion demulsification due to excessive rotation speed, thus achieving an optimal balance between dispersion efficiency and system stability. Filtering with a 200-mesh screen effectively traps small amounts of incompletely dispersed large particles or agglomerates, ensuring the finished coating has the required fineness and smooth application, preventing nozzle clogging during spraying or particulate surface defects during brushing. This optimized combination of process parameters further improves batch-to-batch stability and film appearance quality, providing a process guarantee for obtaining high-quality coatings with consistent performance and a smooth surface.
[0067] By controlling the high-speed dispersion speed within the range of 1500–2500 rpm, sufficient shear force can be provided to break up filler agglomerates and achieve submicron-level dispersion (fineness ≤30μm), while avoiding excessive heat generation or polymer emulsion demulsification caused by excessive speed, thus achieving the best balance between dispersion efficiency and system stability.
[0068] High-speed dispersion is a key step in coating preparation. The rotation speed must be selected to balance dispersion efficiency and system stability: if the rotation speed is too low, the shear force is insufficient and the fineness cannot be achieved; if the rotation speed is moderate, it provides sufficient shear force to depolymerize the aggregates without damaging the stability of the polymer emulsion; if the rotation speed is too high, the strong shear force will destroy the double electric layer structure of the latex particles, leading to demulsification or flocculation.
[0069] After experimental verification, when the dispersion speed is 1500 rpm, the fineness (D90) is 30 μm, the system temperature is 32℃, there is no demulsification, the adhesion is grade 0, and the coating gloss is 72%. When the dispersion speed is 2000 rpm, the fineness (D90) is 25 μm, the system temperature is 35℃, there is no demulsification, the adhesion is grade 0, and the coating gloss is 82%. When the dispersion speed is 2500 rpm, the fineness (D90) is 23 μm, the system temperature is 38℃, there is no demulsification, the adhesion is grade 0, and the coating gloss is 85%. When the dispersion speed is 3000 rpm, the fineness (D90) is 20 μm, the system temperature is 52℃, severe demulsification occurs, the adhesion is grade 2, and the coating gloss is 51%.
[0070] In summary, a dispersion speed within the range of 1500–2500 rpm can achieve a fineness of ≤30 μm, a system temperature of ≤38℃, no demulsification, adhesion grade 0, and a coating gloss of 72–85%. 2000 rpm is the optimal setting. Exceeding this range, such as 3000 rpm, demulsification occurs, adhesion drops to grade 2, and gloss decreases.
[0071] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions above are merely illustrative of the principles of the invention. Various changes and modifications can be made to the present invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents. Any aspects not detailed in the present invention are well-known to those skilled in the art.
Claims
1. A water-based environmentally friendly epoxy paint, characterized in that: It is composed of component A and component B in a weight ratio of 100:15 to 30; Component A comprises the following raw materials in parts by weight: 40-65 parts of waterborne epoxy resin emulsion; 10-20 parts of modified core-shell structured acrylate copolymer; 3-8 parts of polyaniline-modified zinc phosphate; 5-12 parts of composite flame retardant; 0.5-2.0 parts of wetting and dispersing agent; Defoamer 0.2-1.0 parts; deionized water 10-25 parts; Component B comprises the following raw materials in parts by weight: 80-95 parts of water-based epoxy curing agent; 5-15 parts of adhesion promoter; The modified core-shell structured acrylate copolymer is a core-shell structured emulsion with methyl methacrylate as the core and butyl acrylate-hydroxyethyl acrylate-vinyltriethoxysilane copolymer as the shell, and its glass transition temperature is -10℃ to 15℃, and its solid content is 40% to 50%. The preparation method of the polyaniline-modified zinc phosphate is as follows: zinc phosphate is dispersed in an ethanol aqueous solution, aniline monomer and ammonium persulfate are added, and polymerization reaction is carried out at 0-5℃ for 4-8 hours. After filtration, washing and drying, polyaniline-coated zinc phosphate composite particles are obtained. The composite flame retardant is composed of the following components in parts by weight: 30-50 parts of aluminum diethylphosphinic acid, 20-40 parts of melamine polyphosphate, 10-20 parts of zinc borate, and 5-15 parts of expanded graphite.
2. The water-based environmentally friendly epoxy paint according to claim 1, characterized in that: The adhesion promoter is A mixture of glycidyl etheroxypropyltrimethoxysilane and titanate coupling agent in a weight ratio of 3:1 to 1:
1.
3. The water-based environmentally friendly epoxy paint according to claim 2, characterized in that: The wetting and dispersing agent is a polyether-modified polysiloxane, and the defoamer is a polyether-modified organosilicon defoamer.
4. The method for preparing water-based environmentally friendly epoxy paint according to any one of claims 1-3, characterized in that: Includes the following steps: (1) Preparation of component A: Mix deionized water, wetting and dispersing agent and defoamer evenly according to the formula. Add polyaniline modified zinc phosphate and composite flame retardant in sequence under stirring. Disperse at high speed for 30-60 min until fineness ≤30μm. Then adjust the stirring speed, add waterborne epoxy resin emulsion and modified core-shell structure acrylate copolymer, continue stirring for 20-40 min, and filter out the material. (2) Preparation of component B: Mix the water-based epoxy curing agent and adhesion promoter evenly and stir for 10-20 minutes; (3) When using, mix component A and component B in proportion and let stand for 10 to 20 minutes to mature.
5. The preparation method according to claim 4, characterized in that: In step (1), the high-speed dispersion speed is 1500-2500 rpm, and the filtration uses a 200-mesh filter.
Citation Information
Patent Citations
Preparation methods of flame-retardant, waterproof, water-based core-shell resin coatings and paints
CN112266679B
Polyaniline-zinc phosphate-aluminum triphosphate composite waterborne epoxy resin anticorrosive paint and preparation method thereof
CN116948496A
Water-based industrial anti-rust paint for steel components and preparation method of water-based industrial anti-rust paint
CN121450203A
Fireproof sealing coating composition for glass fiber ceramic fiber felt
CN121495411A
Composite flame retardant, preparation method and application thereof, and thermosetting powder coating
CN122080681A
